Phenotypic plasticity and carryover effects in an ecologically important bivalve in response to changing environments - Alma, Lindsay; McElhany, Paul; Crim, Ryan N.; Newton, Jan A.; Maher, Michael; Mickett, John B.; Padilla-Gamiño, Jacqueline L. (Frontiers in Marine Science, 2024)
Phenotypic plasticity can improve an organism’s fitness when exposed to novel environmental conditions or stress associated with climate change. Our study analyzed spatiotemporal differences in phenotypic plasticity and offspring performance in Olympia oysters Ostrea lurida. This species is an ecosystem engineer and is of great interest for commercial and restoration aquaculture. We used a multidisciplinary approach to examine acute and long-term physiological differences in O. lurida in response to in situ oceanographic conditions in a dynamic inland sea. We outplanted oysters to different areas in Puget Sound, Washington, affixing cages to anchor lines of oceanographic monitoring buoys. This allowed us to couple high-resolution oceanographic data with organism’s phenotypic response. To assess spatiotemporal differences in oyster physiological performance, we collected oysters after six-months and one year of acclimatization at four field sites. During each collection period we evaluated changes in shell properties, diet, metabolism, and reproduction. Adult growth, δ13C and δ15N isotopic signatures, and gametogenesis were affected by both seasonal and environmental conditions. In the winter, oysters from all sites had higher respiration rates when exposed to acute thermal stress, and lower respiration response to acute pH stress. Lipid content, sex ratio and shell strength were unchanged across locations. Offspring growth rates between sites at experimental temperature 20°C closely reflected parental growth rate patterns. Offspring survival was not correlated with growth rates suggesting different energetic trade-offs in oyster offspring. The metabolic response (respiration) of larvae reached its highest point at 20°C but sharply decreased at 25°C. This indicates that larvae are more sensitive to temperature stress, as adults did not exhibit a reduction in metabolic response at 25°C. By deploying genetically similar oysters into distinct environments and employing a wide range of physiological methodologies to examine performance and fitness, our results indicate that Olympia oysters exhibit a high degree of phenotypic plasticity and show evidence of parental carryover.